2019
DOI: 10.17116/jnevro2019119081130
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of application of acetyl-L-carnitine in neurology and psychiatry (the treatment of polyneuropathy and depressive states)

Abstract: Резюме Ацетил-L-карнитин (АЛК)-биологически активная форма L-карнитина. Механизм действия АЛК на ткани мозга заключается в значимом снижении количества потребляемого кислорода для энергетического обеспечения функции ЦНС. AЛК также обладает антиоксидантной и антиапоптотической активностью, модулирующим влиянием на синаптическую передачу. Сходство по структуре с ацетилхолином позволяет оказывать холиномиметическое действие, а также проявлять нейропротективные и нейротрофические свойства. AЛК оказывает антидепрес… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…ALC exhibits a variety of physiological activities, including nutritional effects, neuroprotective effects, analgesic effects of the peripheral nervous system, antioxidant effects, and plays important roles in the functioning of male reproductive system. Commercially, ALC‐based drugs are mainly used to improve male fertility, treat Alzheimer’s disease, hepatic encephalopathy, depression, and diabetic peripheral neuropathy (Anikin, Makhova, & Shikh, 2019; Di Stefano, Di Lionardo, Galosi, Truini, & Cruccu, 2019; Gamidov, Ovchinnikov, & Popova, 2019; Jeong et al, 2017; Ponomareva, 2017; Rolim, da Silva, Flumignan, Abreu, & Dib, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…ALC exhibits a variety of physiological activities, including nutritional effects, neuroprotective effects, analgesic effects of the peripheral nervous system, antioxidant effects, and plays important roles in the functioning of male reproductive system. Commercially, ALC‐based drugs are mainly used to improve male fertility, treat Alzheimer’s disease, hepatic encephalopathy, depression, and diabetic peripheral neuropathy (Anikin, Makhova, & Shikh, 2019; Di Stefano, Di Lionardo, Galosi, Truini, & Cruccu, 2019; Gamidov, Ovchinnikov, & Popova, 2019; Jeong et al, 2017; Ponomareva, 2017; Rolim, da Silva, Flumignan, Abreu, & Dib, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that abortion can cause varying degrees of physical and mental harm to women, and in some cases, may lead to death [3]. The mental state of women with induced elective termination of pregnancy is often related to various postoperative diseases, especially postoperative depression [4]. Depression, a mental disorder characterized by persistently depressed mood, is a common disease that endangers human physical and mental health.…”
Section: Introductionmentioning
confidence: 99%